The Advantages and Disadvantages of Social Networks in Modern Society - Akromova , Zilola (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This article analyzes the role of social networks in modern society, as well as their advantages and disadvantages. While social networks expand opportunities for communication, access to information, and education, their negative impact on human psychology, time management, and social relationships is also considered. The article emphasizes the importance of using social networks wisely and effectively.